Application of program for nurse’s management about care of children treated with Ventricular Peritoneal Shunt - Raghda Lazem Mahmoud, Adraa Hussain Shawq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hydrocephalus management present as a significant challenge for child, parents, and multidisciplinary health care team. Despite the advancements in shunt technology and neurosurgery treatment techniques, many children with hydrocephalus reported high rates of shunt failure and require shunt revision or replacement. Infants are more susceptible than older children to die as a result of shunt failure, which caused by variety of reasons such as prematurity, low birth weight, infection. Material and Method: The sample of the study was chosen purposive (non-probability). Which consist of (30) nurses from morning and evening shift. The sample of the study was collected from Ibn Sina Teaching Hospital, who provides nursing care service for children with Ventricular Peritoneal Shunt, collected from the places (intensive care unit and wards of neurosurgery in hospital). Results: The results showed that the nurses sample in the study, that 73.3% (22) of the sample at age (20-29) years with mean (1.33) and standard deviation (0.606), 60.0% (18) of the sample was female gender with mean (1.60) and standard deviation (0.498), 46.7% (14) of them was bachelor in nursing of educational level with mean (2.30) and standard deviation (0.750). Conclusion: The study concluded that the nurses’ practice about care for children treatment with ventricular peritoneal shunt was acceptance.